The Effect Of Temperature On Recombinant Human Granulocyte Colony Stimulating Factor Production By Pichia pastoris Expression System - Adiredja, Yuliawati; Fuad, Asrul Muhamad (Indonesian Journal of Pharmacy, 2018)
Granulocyte colony stimulating factor (G-CSF) is a haematopoetic growth factor that functions as specific stimulator of the survival, proliferation, and differentiation of precursor cells of the neutrophilic granulocyte cell lineage as well as an activator of mature neutrophil function. The main objective of this work is to compare the effect of different temperature on the production of extracellular recombinant G-CSF in Pichia  pastoris. Cells were cultured for 72h in baffled shake-flasks at 20°C, 25°C, and 30°C in two different medium; buffered glycerol/methanol-complex medium (BMGY/BMMY) and buffered minimal glycerol/methanol (BMGH/BMMH) after methanol induction every 12h. Expressed recombinant hG-CSF in the methylotrophic yeast P. pastoris was analyzed with SDS-PAGE. The 23 kDa protein was secreted into the culture supernatant when induced with methanol. Production of recombinant G-CSF protein in P. pastoris at 30°C at 48h incubation after methanol induction every 12h is the highest in both complex and minimum medium.